ANALISIS KEBUTUHAN PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA KESEHATAN BERBASIS INTEGRATED PHYSICAL EDUCATION DI SEKOLAH DASAR - Saryono, Soni Nopembri (Jurnal Pendidikan Jasmani Indonesia, 2013)
The purpose of this study is to analyze the various learning needs to proper integrated physical education withother subjects. The study was a descriptive analytic qualitative approach. The subjects were 12 physical educationteachers and 9 classroom teachers in the city of Yogyakarta. The data collecting in this study used Focused GroupDiscussion (FGD), interviews, observation, and documentation. The instrument of the study is FGD and structuredinterview guide, observation and documentation sheet. Analysis of the data used a qualitative data analysis. Thisstudy has uncovered a variety of needs integrated physical education with other subjects. The needs are (1) anunderstanding of the purpose of equalization physical education comprehensively, (2) intensive discussions betweenphysical teachers and classroom teachers to identify appropriate SKKD, and (3) mutual collaboration between physicaleducation teachers and classroom teachers to develop infrastructure and instructional media. Integrated physicaleducation with other subjects is expected to be one of the future alternative learning innovations in primary schools.Keywords: Learning, Integration, Penjasorkes, Elementary School.